4x - 2x - 5 = 4 + 6x + 3 |
Goal is to isolate x on one side to be able to solve. |
2x - 5 = 7 + 6x |
Combine like terms. |
2x - 5 + 5 = 7 + 6x + 5 |
Add 5 to each side. |
2x = 12 + 6x |
Subtract 6x from each side. |
-4x = 12 |
Then, divide both sides by -4 |
x = -3 |
CHECK your solution by plugging back into the original equation. |
Disclaimer: I did not create nor do I own these videos. I have simply embedded them, courtesy of YouTube. (But I do think this teacher does a fantastic job with his video tutorial series.)